SMART CITIES FOR ALL: LEVERAGING TECHNOLOGY TO REDUCE URBAN INEQUALITY - Nursanty, Eko; Rusmiatmoko, Djudjun (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2024)
This research paper delves into the transformative potential of technology to address urban inequality, a persistent challenge faced by urban centers marked by income disparity, limited access to essential services, and spatial segregation. Employing a multi-disciplinary approach, the study integrates insights from urban planning, social sciences, and technology innovation. Beginning with an extensive literature review, the research identifies key manifestations of inequality in cities and explores the ways technology has been harnessed to mitigate disparities in education, healthcare, transportation, housing, and public services, drawing from successful case studies and underlying principles that facilitated their success. The study also addresses the challenges and limitations associated with technology driven solutions, including ethical considerations, digital divides, and potential unintended consequences, while investigating the role of public-private partnerships and policy frameworks in supporting technology-driven initiatives to reduce urban inequality. Presenting a comprehensive framework, the paper outlines various technological interventions and innovative strategies, ranging from smart city infrastructure and data-driven decision-making to inclusive digital platforms and community-driven solutions, all adaptable to specific urban contexts. In conclusion, the research offers actionable recommendations for policymakers, city planners, and technology developers to effectively utilize technology in reducing urban inequality, emphasizing collaborative efforts, participatory design, and continuous evaluation to ensure equitable distribution of benefits from technology-enabled urban development. By analyzing successful case studies and addressing potential challenges, this study provides valuable insights to create more inclusive cities through the judicious application of technology, fostering a broader dialogue among stakeholders and encouraging the adoption of innovative and ethical practices to establish sustainable, just, and equal urban spaces.